Spiritual Quotient Zohar dan Marshall Perspektif Pendidikan Islam - Arin Muflichatul M. (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2021)
This study is intended to answer the following problems: (1) What is the general concept of Spiritual Quotient? (2) What is the concept of spiritual quotient in Islamic Education Perspective? This article belongs to the type of library research, which is a series of activities related to the method of collecting library data, reading, taking notes, and processing research materials which are library research or pure research. All data were analyzed with a philosophical approach (Philosophical Approach). This study shows that: (1) Spiritual intelligence means the ability to know and understand ourselves fully as spiritual beings and as part of the universe. Western SQ is more oriented to the completion and achievement of worldly happiness, while Islamic SQ is more to the achievement of world and hereafter happiness. If both are used ideally, SQ can be implemented to achieve